Cross-Cultural Online Education: Benefits, Challenges, and Solutions - Changiz Mohiyeddini (Online Learning In Educational Research (OLER), 2024)
The objective of this article is to explore the benefits and challenges of cross-cultural online education and propose solutions to promote inclusivity and equity in a globalized educational context. Pervasive forms of cross-cultural dynamics are prevalent within our globalized and digitalized educational systems. It is within this global context that contemporary educational systems operate and seek success. By removing geographical and economic barriers, online education has transformed higher education, enabling students from diverse backgrounds to access previously inaccessible programs. This democratization of education promotes educational equity. It increases the chances for students from various socioeconomic backgrounds to access high- quality education and enroll in courses globally without relocating. However, cultural diversity presents challenges for establishing inclusive and equitable cross-cultural online education. As the first paper to specifically discuss cross-cultural dynamics in online education, this work highlights these challenges and offers solutions to ensure that cross-cultural online education remains inclusive and equitable